New Amphibolips gallwasp species from Mexico (Hymenoptera: Cynipidae) - Melika, G.; Equihua-Martínez, A.; Estrada-Venegas, E. G.; Cibrián-Tovar, D.; Cibrián-Llanderal, V. D.; Pujade-Villar, J. (Zootaxa, 2011)
Two new species of oak gallwasp, Amphibolips zacatecaensis Melika & Pujade-Villar and A. hidalgoensis Pujade-Villar & Melika, are described from Mexico, known to induce galls on Quercus eduardi, Q. crassipes, Q. candicans and Q. crassifolia (section Lobatae, red oaks). Only females are known. Data on the diagnosis, distribution and biology of the new species are given.